Pharmacogenomic Determinants of the Cardiovascular Effects of Dalcetrapib. (April 2015) - Tardif, Jean-Claude; Rhéaume, Eric; Lemieux Perreault, Louis-Philippe; Grégoire, Jean C.; Feroz Zada, Yassamin; Asselin, Géraldine; Provost, Sylvie; Barhdadi, Amina; Rhainds, David; L'Allier, Philippe L.; Ibrahim, Reda; Upmanyu, Ruchi; et al.
<x xml:space="preserve">Abstract</x> Background— Dalcetrapib did not improve clinical outcomes, despite increasing high-density lipoprotein cholesterol by 30%. These results differ from other evidence supporting high-density lipoprotein as a therapeutic target. Responses to dalcetrapib may vary according to patients' genetic profile. Methods and Results— We conducted a pharmacogenomic evaluation using a genome-wide approach in the dal-OUTCOMES study (discovery cohort, n=5749) and a targeted genotyping panel in the dal-PLAQUE-2 imaging trial (support cohort, n=386). The primary endpoint for the discovery cohort was a composite of cardiovascular events. The change from baseline in carotid intima-media thickness on ultrasonography at 6 and 12 months was evaluated as supporting evidence. A single-nucleotide polymorphism was found to be associated with cardiovascular events in the dalcetrapib arm, identifying the ADCY9 gene on chromosome 16 (rs1967309; P=2.41×10–8), with 8 polymorphisms providing P<10–6 in this gene. Considering patients with genotype AA at rs1967309, there was a 39% reduction in the composite cardiovascular endpoint with dalcetrapib compared with placebo (hazard ratio, 0.61; 95% confidence interval, 0.41–0.92). In patients with genotype GG, there was a 27% increase in events with dalcetrapib versus placebo. Ten single-nucleotide polymorphism in the ADCY9 gene, the majority in linkage disequilibrium with rs1967309, were associated with the effect of dalcetrapib on intima-media thickness (P<0.05). Marker rs2238448 in ADCY9, in linkage disequilibrium with rs1967309 (r2=0.8), was associated with both the effects of dalcetrapib on intima-media thickness in dal-PLAQUE-2 (P=0.009) and events in dal-OUTCOMES (P=8.88×10–8; hazard ratio, 0.67; 95% confidence interval, 0.58–0.78). Conclusions— The effects of dalcetrapib on atherosclerotic outcomes are determined by correlated polymorphisms in the ADCY9 gene. Clinical Trial Information— URL: http://www.clinicaltrials.gov. Unique identifiers: NCT00658515 and NCT01059682